MicroRNA-31 reflects IL-6 expression in cancer tissue and is related with poor prognosis in bile duct cancer. (30th May 2018) - Ishigami, Keisuke; Nosho, Katsuhiko; Koide, , Hideyuki; Kanno, Shinichi; Mitsuhashi, Kei; Igarashi, Hisayoshi; Shitani, Masahiro; Motoya, Masayo; Kimura, Yasutoshi; Hasegawa, Tadashi; Kaneto, Hiroyuki; Takemasa, Ichiro; et al.
Abstract : Mir-31 high expression was significantly associated with poor prognosis in patients with bile duct cancer. The IL-6-STAT-3 signalling pathway regulated bile duct cancer cell proliferation and miR-31 expression. MiR-31 may be a promising biomarker that reflects IL-6 expression in bile duct cancer tissues and predicts poor prognosis. Abstract: Bile duct cancer is a highly aggressive malignancy wherein early diagnosis is difficult and few treatment options are available. MicroRNA-31 (miR-31) is reported to be related with survival in patients with gastrointestinal cancers; however, the regulatory mechanism of miR-31 and association between miR-31 expression and survival in patients with bile duct cancer cases have not been established. Thus, we evaluated miR-31 expression in bile duct cancer tissues and assessed its relationship with prognosis. Additionally, we examined the effects of several cytokines on miR-31 expression. The study included 81 samples of bile duct cancer tissues. MiR-31 expression in bile duct cancer cells was significantly higher than that in normal bile duct epithelial cells ( P = 0.038). There were no significant associations between miR-31 expression and clinical or pathological characteristics, except for tumour size ( P = 0.012). In Kaplan–Meier analysis, high miR-31 expression was significantly associated with shorter survival (log-rank test, P = 0.0082). In multivariate Cox regression analysis, high miR-31 expression was significantly associated with prognosis ( P = 0.043), independent of clinical or pathological features. Interleukin-6 (IL-6) significantly promoted miR-31 expression and cell proliferation in a dose-dependent manner, and the inhibition of STAT-3 signalling significantly suppressed miR-31 expression and cell proliferation. In conclusion, high expression was significantly associated with poor prognosis in bile duct cancer patients. The IL-6-STAT-3 signalling regulated bile duct cancer cell proliferation and miR-31 expression. Our findings suggest that miR-31 may be a promising biomarker that reflects IL-6 expression in bile duct cancer tissues and predicts poor prognosis.